2017
DOI: 10.1002/14651858.cd011719.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Remote ischaemic preconditioning for coronary artery bypass grafting (with or without valve surgery)

Abstract: We found no evidence that RIPC has a treatment effect on clinical outcomes (measured as a composite endpoint including all-cause mortality, non-fatal myocardial infarction or any new stroke, or both, assessed at 30 days after surgery). There is moderate-quality evidence that RIPC has no treatment effect on the rate of the composite endpoint including all-cause mortality, non-fatal myocardial infarction or any new stroke assessed at 30 days after surgery, or both. We found moderate-quality evidence that RIPC re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
33
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 83 publications
0
33
0
2
Order By: Relevance
“…Similar findings were observed in the ERICCA Study including 1612 surgery cardiac patients with no significant benefits 1 year after surgery. Very recently, we performed a Cochrane meta‐analysis and found no evidence that RIPC has a treatment effect on clinical outcomes (measured as a composite end point including all‐cause mortality, non‐fatal myocardial infarction or any new stroke, or both, assessed at 30 days after surgery), while we found moderate‐quality evidence that RIPC reduces the cardiac troponin T and I release measured at 72 hours after surgery.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Similar findings were observed in the ERICCA Study including 1612 surgery cardiac patients with no significant benefits 1 year after surgery. Very recently, we performed a Cochrane meta‐analysis and found no evidence that RIPC has a treatment effect on clinical outcomes (measured as a composite end point including all‐cause mortality, non‐fatal myocardial infarction or any new stroke, or both, assessed at 30 days after surgery), while we found moderate‐quality evidence that RIPC reduces the cardiac troponin T and I release measured at 72 hours after surgery.…”
Section: Discussionmentioning
confidence: 73%
“…Similar findings were observed in the ERICCA Study 9 including 1612 surgery cardiac patients with no significant benefits 1 year after surgery. Very recently, we performed a Cochrane meta-analysis 21 and found no evidence that RIPC has a treatment effect on shown for the two intervention groups. Event-free survival did not differ significantly between the two intervention groups (Cox regression analysis, with adjustment for the stratification variables).…”
Section: Discussionmentioning
confidence: 98%
“…Several approaches have been implemented to reduce the risk during surgery (hypothermia, cardioplegic solutions, and the limitation of procedure times). These strategies have led to a pronounced reduction in mortality and morbidity; however, biomarkers of ischemia indicate persisting postoperative myocardial damage [10,11].…”
Section: Discussionmentioning
confidence: 99%
“…They found that women were older than men and had different risk factors compared to men, these results were in accordance to ours. Benstoem et al (18) studied remote ischemic preconditioning for coronary artery bypass grafting and found that the mean age of his patients was 64± 11.5 years old. The age incidence of MI was earlier in Saudi Arabia, Khalid et al (19) concluded that the mean age ± SD of his MI patients was 58 ± 12.9 years in Saudi nationals on searching the baseline characteristics, management practices, and in-hospital outcomes of patients with acute coronary syndromes in the Saudi project for assessment of coronary events (SPACE) registry.…”
Section: Discussionmentioning
confidence: 99%